Inhibitor scaffolds for 2-oxoglutarate-dependent histone lysine demethylases. - Rose, N; Ng, S; Mecinović, J; Liénard, B; Bello, S; Sun, Z; McDonough, M; Oppermann, U; Schofield, C (2008)
The dynamic methylation of histone lysyl residues plays an important role in biology by regulating transcription, maintaining genomic integrity, and by contributing to epigenetic effects. Here we describe a variety of inhibitor scaffolds that inhibit the human 2-oxoglutarate-dependent JMJD2 subfamily of histone demethylases. Combined with structural data, these chemical starting points will be useful to generate small-molecule probes to analyze the physiological roles of these enzymes in epigenetic signaling.